2016
DOI: 10.1080/19439342.2016.1231704
|View full text |Cite
|
Sign up to set email alerts
|

Impact and cost-effectiveness of women's training in home gardening and nutrition in Bangladesh

Abstract: This study quantifies the impact and cost-effectiveness of training poor rural women in Bangladesh in home gardening and nutrition. We use baseline and follow-up data for 646 intervention and control households and apply a difference-in-difference estimator. We find that the intervention significantly (p < 0.01) increased vegetable production (+16.5 g/person/day), vegetable consumption and the micronutrient supply from the garden. Using the disability-adjusted life years (DALYs) approach, we show that the inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
55
0
2

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 25 publications
4
55
0
2
Order By: Relevance
“…This might be due to women who had home gardening would have chance of eating diversified food regularly and may contribute to appropriate weight. This finding was consistent with prior studies in Cambodia, Nepal, and Philippines [ 39 , 40 ].…”
Section: Discussionsupporting
confidence: 94%
“…This might be due to women who had home gardening would have chance of eating diversified food regularly and may contribute to appropriate weight. This finding was consistent with prior studies in Cambodia, Nepal, and Philippines [ 39 , 40 ].…”
Section: Discussionsupporting
confidence: 94%
“…There is growing interest in the potential of home‐based food production to address micronutrient undernutrition in developing countries (e.g., Keatinge et al, ; Olney, Pedehombga, Ruel, & Dillon, ; Weinberger, ). Home gardens can be a useful food‐based strategy to promote more balanced diets amongst poor rural HHs that have access to a small plot of land and are willing to engage in gardening (Schreinemachers, Patalagsaand, & Uddin, ). Studies conducted in Bangladesh, Cambodia, Nepal, and the Philippines found that families who participated in homestead food production activities benefited from increased production and consumption of vegetables, fruits, and poultry products (Helen Keller International, ).…”
Section: Discussionmentioning
confidence: 99%
“…For the subsequent six months, the visiting frequency was monthly. The average cost of the intervention was about USD 55.3 per home garden, including all direct and indirect project costs (Schreinemachers et al 2016). The project was funded by the United States Agency for International Development (USAID) and implemented by the World Vegetable Center in partnership with the non-governmental organizations BRAC and Proshika.…”
Section: The Home Garden Interventionmentioning
confidence: 99%
“…There is growing evidence that integrated home garden interventions are effective in increasing the consumption of nutritious food among poor rural households in developing countries (Olney et al 2009(Olney et al , 2013Schreinemachers et al 2016;Tesfamariam et al 2018;Osei et al 2017). Several recent reviews have identified that such interventions are one of few agricultural interventions with a proven impact on increased vegetable consumption, although the evidence basis for nutritional status remains weak (DFID 2014;Ruel et al 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation